Striving for progress in Arab-German training co-operation - Niediek, Silvia [Verfasser] (My University, 2015)
"The demands on companies, their services and their employees' professional qualification are constantly subject to change in today's globalized economy. However, the ability to handle modern technologies and a high degree of competence in solving problems continue to be taken for granted and remain important for all employees. The productivity and competitive capability of companies competing in the global markets can be strengthened in the long term only by systematically developing and expanding employee skills and knowledge. Not only businesses benefit from vocational education. It also provides a safeguard for employability and career opportunities and contributes to the sustained social stability of entire countries." (author, BIBB-Doku)
Keywords: I 1.1 Systemberatung; I 2.3 Außereuropäische Regionen; I 2.1 Deutschland; Berufsbildung; Internationale Zusammenarbeit; Arabische Länder; Bundesrepublik Deutschland